2018
DOI: 10.1007/s13765-018-0366-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of γ-aminobutyric acid and isoflavone contents during the fermentation of high-protein soy powder yogurt with Lactobacillus brevis

Abstract: This study evaluated the changes in c-aminobutyric acid (GABA) and isoflavone aglycone contents from soy powder yogurt (SPY) due to sprouting of soybean (1 cm) and fermentation with Lactobacillus brevis. The levels of GABA and the aglycone form increased, and the glutamate decarboxylase and b-glucosidase activities increased; however, the isoflavone glycoside and malonylglycoside contents decreased after fermentation for 72 h. In particular, after 60 h, the SPY presented the highest GABA content (120.38 mg/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
1
8
3
Order By: Relevance
“…plantarum NTU 102 was 440 mg/L and 629 mg/L, respectively (Song & Yu, 2018;Tung, Lee, Liu, & Pan, 2011) which was also lower than those obtained in our study. However, fermented skim milk or germinated soybean extract with LAB isolated from traditional fermented foods had a higher GABA content than our results (Hwang et al, 2018;Park & Oh, 2007;Seo et al, 2013;Shan et al, 2015). Yogurt-type soy product prepared from Monascus-fermented soybean extract and soymilk increased the GABA content from 24.6 to 68.6 mg/100 g dw, equivalent from 1640 to 4600 mg/L, when incubated by a mix of Lb.…”
Section: Fermentation Of Soymilk Hydrolysate At the Bacterial Growth contrasting
confidence: 75%
See 1 more Smart Citation
“…plantarum NTU 102 was 440 mg/L and 629 mg/L, respectively (Song & Yu, 2018;Tung, Lee, Liu, & Pan, 2011) which was also lower than those obtained in our study. However, fermented skim milk or germinated soybean extract with LAB isolated from traditional fermented foods had a higher GABA content than our results (Hwang et al, 2018;Park & Oh, 2007;Seo et al, 2013;Shan et al, 2015). Yogurt-type soy product prepared from Monascus-fermented soybean extract and soymilk increased the GABA content from 24.6 to 68.6 mg/100 g dw, equivalent from 1640 to 4600 mg/L, when incubated by a mix of Lb.…”
Section: Fermentation Of Soymilk Hydrolysate At the Bacterial Growth contrasting
confidence: 75%
“…brevis OPY-1 at 30 • C, the initial GABA level was very low but yogurt with a GABA content of 425 μg/g dw was produced after 24 h fermentation (Park & Oh, 2007). Other studies reported the production of GABA-enriched soy-yogurt and skim milk at 30 • C (Hwang et al, 2018;Seo et al, 2013). In our study, although Glu was still present in high amounts but GABA was not further produced at this fermentation condition.…”
Section: Fermentation Of Soymilk Hydrolysate At the Bacterial Growth contrasting
confidence: 54%
“…After 60 h, the highest concentration of GABA (120.38 mg/100 mL) was detected, together with a significant increase of isoflavone aglycones (daidzein, glycitein, and genistein), resulting from the high β-glucosidase activity, and increase of the antioxidant activity. This process resulted in a functional PYBL [ 37 ].…”
Section: Nutritional and Functional Aspects: Matrix- And Fermentatmentioning
confidence: 99%
“…For ethanol extraction, 100 mL of 50% ethanol was added to 10 g of each sample and extracted at 300 rpm for 12 h. The extracts were filtered at 0.45 μm and lyophilized at −70 °C. The extract preparation process was standardized as previously described [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, 5% (v/v) of 1:1 mixture of Lactobacillus plantarum (P1201) and Lactobacillus brevis (BMK184) was injected and fermented at 30 • C for 5 days. All samples were dried at 55 • C for 3 days, pulverized, and stored at −20 • C. For ethanol extraction, 100 mL of 50% ethanol was added to 10 g of each sample and extracted at 300 rpm for 12 h. The extracts were filtered at 0.45 µm and lyophilized at −70 • C. The extract preparation process was standardized as previously described [17,18].…”
Section: Preparation Of Pg Extractsmentioning
confidence: 99%